Primula calderiana subsp. bawaii (Primulaceae): a new subspecies from Arunachal Pradesh, India - Bawri, Amal; Gajurel, Padma Raj; Khan, Mohammed Latif (Phytotaxa, 2016)
A new subspecies Primula calderiana subsp. bawaii, from Arunachal Pradesh is described and illustrated. The complete description with illustrations and colour plate is provided for easy identification. Its conservation status is assessed as Critically Endangered as per IUCN.